Predicting the behavioral impact of transcranial direct current stimulation: issues and limitations - De Berker, Archy O.; Bikson, Marom; Bestmann, Sven (Frontiers in Human Neuroscience, 2013)
The transcranial application of weak currents to the human brain has enjoyed a decade of success, providing a simple and powerful tool for non-invasively altering human brain function. However, our understanding of current delivery and its impact upon neural circuitry leaves much to be desired. We argue that the credibility of conclusions drawn with tDCS is contingent upon realistic explanations of how tDCS works, and that our present understanding of tDCS limits the technique’s use to localize function in the human brain. We outline two central issues where progress is required: the localization of currents, and predicting their functional consequence. We encourage experimenters to eschew simplistic explanations of mechanisms of transcranial current stimulation. We suggest the use of individualized current modelling, together with computational neurostimulation to inform mechanistic frameworks in which to interpret the physiological impact of tDCS. We hope that through mechanistically richer descriptions of current flow and action, insight into the biological processes by which transcranial currents influence behaviour can be gained, leading to more effective stimulation protocols and empowering conclusions drawn with tDCS.